2021
DOI: 10.3390/electronics10040414
|View full text |Cite
|
Sign up to set email alerts
|

Buck-Boost/Flyback Hybrid Converter for Solar Power System Applications

Abstract: This paper proposes a hybrid converter to supply power from solar power source to load. Since power is generated by solar power, which depends on the intensity of solar power, the power generated by the solar power does not keep at a constant power. Therefore, the proposed system needs a battery to balance power between solar power and load. When the proposed one uses the battery to balance powers, the proposed circuit requires a charger and discharger. To simplify the proposed converter, a buck-boost converte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Tseng et al reported "Buck-Boost/Flyback Hybrid Converter for Solar Power System Applications" [1]. In this paper, the authors propose a hybrid converter to supply power from solar power source to load.…”
Section: The Topics Of Intelligent Electronic Devices and Its Applica...mentioning
confidence: 99%
“…Tseng et al reported "Buck-Boost/Flyback Hybrid Converter for Solar Power System Applications" [1]. In this paper, the authors propose a hybrid converter to supply power from solar power source to load.…”
Section: The Topics Of Intelligent Electronic Devices and Its Applica...mentioning
confidence: 99%
“…Currently, the improvement of the power electronic equipment has led to momentous growth in many industrial segments, such as e-mobility or renewable energy (Pesce et al, 2021;Ramos-Paja et al, 2021;Tseng and Fan, 2021). A common feature of the above industrial segments is that the auxiliary circuits of the equipment require a stable direct current (DC) voltage, which is achieved by a DC/DC or alternating current (AC)/DC converter.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the efficiency of the SPV system, MPPT algorithm is much needed. Though there are many MPPT algorithms in the literature, P&O algorithm is the simplest one which works towards maximum power point using operating point irrespective of the atmospheric conditions, aging, etc., Generally this method compares the SPV current (Ipv) and SPV voltage (Vpv), introduce delay then controls the values of Ipv and Vpv, resulting in less system response, fluctuation in finding MPP during steady state [1][2][3]. To overcome the issue mentioned, this work proposes a modified P&O algorithm that adjusts hysteresis bandwidth & reference step size.…”
Section: Introductionmentioning
confidence: 99%